Comparison Of The Effectiveness Of Oxytocin Massage And Marmet Technique In Increasing Breast Milk Production In Postpartum Mothers: A Quasi-Experimental Study - Norlaila Sofia (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2024)
Research Metodes: The research employ a quasi-experimental design with a pre-test and post-test approach. The sample consist of 60 pospartum mothers divided two group: the oxytocin massage group (n=30) and the marmet technique group (n=30). The intervention was conducted over 14 days, and breast milk production was measured using indicators of infant weight gain and urination frequency Results: It showed that both techniques are effective in increasing breast milk production; however, oxytocin massage demonstrates a more significant improvement (p<0.05). In conclusion, oxytocin massage can be recommended as a primary intervention to enhance breast milk production in postpartum mothers.